Critical Appraisal of Materials and Methods in Observational Studies Published in Pathology Journals: A Cross-sectional Study - Supriya Siddavatam; BN Kumarguru (Journal of Clinical and Diagnostic Research)
Introduction: Critical appraisal is the craftmanship of scrutinising and assessing the accuracy and credibility of data in published research work. It is of paramount importance to distinguish between scientifically helpful and well-written articles from imprecise and fallacious articles. Critical appraisal of methodology is a crucial prerequisite for medical students, young clinicians and accomplished physicians. However, the critical appraisal of methodology in the studies published in pathology journals has not been thoroughly explored. Aim: To compare and critically evaluate the materials and methods related to aspects of observational studies published in indexed National (Indian) and International (foreign) pathology journals concerning different evaluation parameters. Materials and Methods: A cross-sectional study was conducted in the Department of Pathology at PES University Institute of Medical Sciences (PESU IMSR) in Bengaluru, Karnataka, India and PES Institute of Medical Sciences (PESIMSR) in Kuppam, Andhra Pradesh, India, from September 2023 to October 2023. A total of 50 articles were randomly selected for evaluation using computer-generated random numbers. Out of 50 articles, 25 were selected from National journals and the other 25 were from International journals. The articles were meticulously evaluated concerning materials and methods-related aspects. A total of 15 parameters were evaluated. The first 13 parameters were evaluated for major and minor errors, while the last two parameters were categorised as concordant or discordant. If the parameter was not mentioned, it was considered a major error. If the parameter was mentioned but the information was found to be inadequate, it was considered a minor error. The resulting data were entered into an Microsoft Excel sheet (2021 version) and analysed statistically by using Stata Software (17.0 version). The Chi-square test was employed to analyse the data and the p-value of <0.05 was considered as statistically significant. Results: Out of 15 parameters, study participants, study variables, sample size and methodology procedure details were mentioned in all 50 articles (100%). Study bias was the most underreported parameter, being mentioned in only 7 articles (14%). Major errors were found to be relatively more frequent in the National journals [76 errors (58.46%)] in comparison with the International journals [54 errors (41.54%)]. These values were found to be statistically significant (p=0.030). Minor errors were also relatively more frequent in the National journals [44 errors (51.76%)] in comparison with the International journals [41 errors (48.24%)]. However, these values were not statistically significant (p=0.443). Conclusion: Without a doubt, both National and International pathology journals significantly contribute to the knowledge databases. However, the present study suggested the need for improvement in the quality of publications in both National and International journals concerning the materials and methods-related aspects.